Adherence to Guideline Recommendations in Patients with Thyroid Nodules - Karnchanasorn, Rudruidee; Grdinovac, Kristine; Smith, Nichole; Jani, Bhairvi; Chen, G. John (Kansas Journal of Medicine, 2019)
Introduction. Thyroid nodules are common and fine-needle aspiration (FNA) biopsy is the standard of care for workup to exclude thyroid cancer. In this study, we examined the discrepancy between daily practice and recommended diagnostic approach for management of thyroid nodules, based on history taking, laboratory, and imaging studies. Methods. This was a retrospective chart review of 199 patients who had ultrasound-guided fine needle aspiration (UGFNA) performed at a Midwest academic medical center from January 2010 to December 2011. The quality measures were selected based on recommended clinical practice guidelines, including family history, history of neck radiation, neck symptoms, TSH test, and thyroid ultrasound. Results. The majority of patients were Caucasian females. Family history of thyroid cancer and childhood neck radiation exposure were documented in 79 subjects (40%) and 76 subjects (38%), respectively. Neck symptoms were documented in most subjects, including dysphonia (56.8%), dysphagia (69.9%), and dyspnea (41.2%). Most subjects had a TSH measured and an ultrasound performed prior to biopsy (75% and 86%, respectively). Conclusions. It appears there is a gap between current patient care and clinical practice guidelines for management of thyroid nodules. Clinical history and ultrasound features for risk stratification of UGFNA were lacking, which could reflect physicians’ unfamiliarity with the guidelines. As thyroid nodules are common, enhancing knowledge of the current guidelines could improve appropriate work-up. Further studies are needed to identify factors associated with the poor compliance with clinical guidelines in management of thyroid nodules. KS J Med 2017;10(1):1-2.